Projetos básicos defeituosos e as alterações qualitativas em contratos de obras públicas - Fecuri, Ana Cristina (2022)
Each and every public contracting process, especially those aimed at public works, requires a serious, adequate and efficient administrative planning, developed in the preparatory phase of the administrative proceeding opened for this purpose, when the basic project will be conceived, a technical document able to define the object to be contracted and its specifications, and that will support the bidding and contractual phases. The objective of this study is to investigate the possibility of using the prerogative granted to the Administration to unilaterally and qualitatively alter the object of the administrative contract, given the need to correct basic projects of public works that have correctable defects, so as not to compromise their execution and to give prestige to the public interest. The work developed examines, consequently, if public works contracts in full execution must be declared invalid due to the detection of defects in the elaboration of the basic projects that subsidized them, regardless of the degree of technical and contractual commitment; as well as if the ius variandi may be exercised as an instrument for the correction of defects in the original conception, and, based on this result, under what measure, conditions and limits. The study is based on Law No. 14,133/2021 - the New Bidding and Contracting Law, with Law No. 8,666/1993 as its counterpoint, besides the exploration of the doctrine applied to the theme, the legislative advance, as well as the analysis of the case law of the Federal Audit Court, justified by the excellence of the work developed in the supervision of the use of public resources. The Court of Auditors analyzed the findings of FISCOBRÁS - Annual inspection plan of public works for the years 2015 to 2021, in order to verify the type and extent of the failures found. From the analyses carried out it was found that the due and rigorous administrative planning developed in the preparatory stage of the bidding process is essential to support the preparation of adequate basic projects free of defects, and that the prerogative of unilateral and qualitative modification of the contractual object, as legally conceived, has as its main purpose to modify the project or specifications for a better technical adequacy to the proposed objectives, and not as a tool to correct technical defects of origin. The jurisprudential analysis revealed, however, the widespread use of this instrument for the correction of faulty projects by the Federal Public Administration, as well as its exceptional admission by the Federal Audit Court, which also motivated the federal legislature to contemplate the hypothesis as a legally adequate solution to such purpose. The purpose of these studies, and based on the results obtained, is to understand whether the declaration of nullity or invalidation of public works contracts that contain defects in the technical conception that can be remedied is the only way to restore the offended legality, or whether, in respect for the public interest, the technical flaws detected in basic projects can give rise to unilateral contractual and qualitative changes to their subject matter in an attempt to remedy the contractual defects